Al-P composite oxide and catalyst for purifying exhaust gas using the same

The AL-P composite oxide catalyst addresses the issue of reduced oxidative performance in exhaust gas purification by maintaining a high surface area and acid point distribution, ensuring effective CO and HC oxidation post-high temperature exposure.

JP7621381B2Active Publication Date: 2025-01-24UMICORE SHOKUBAI JAPAN CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022569891
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-16
Filing Date
2021-12-07
Publication Date
2025-01-24
Estimated Expiration
2041-12-07

AI Technical Summary

Technical Problem

Existing exhaust gas purification catalysts fail to demonstrate sufficient oxidative performance for carbon monoxide (CO) and hydrocarbons (HC) in the low temperature range after high temperature durability, necessitating improved catalyst formulations to maintain performance over time.

Method used

A composite oxide catalyst comprising aluminum oxide (Al2O3), zirconium oxide (ZrO2), and phosphorus oxide (P2O5) within specific content ratios, ensuring high surface area and acid point distribution to support precious metals, enhancing CO and HC oxidation even after high temperature exposure.

Benefits of technology

The AL-P composite oxide catalyst maintains a large surface area and acid point distribution, promoting high dispersion of precious metals, thereby improving CO and HC oxidation performance in the low temperature range even after high temperature durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007621381000001
    Figure 0007621381000001
  • Figure 0007621381000002
    Figure 0007621381000002
  • Figure 0007621381000003
    Figure 0007621381000003
Patent Text Reader

Abstract

[Problem] To provide a means for improving the oxidation performance of CO and HC in a low temperature range even after high-temperature endurance test with respect to an exhaust gas purifying catalyst. [Solution] An Al-P composite oxide which contains aluminum oxide and phosphorus oxide, wherein, relative to the total mass of the Al-P composite oxide, the content of the aluminum oxide is from 79% by mass to 97% by mass in terms of Al2O3, the content of zirconium oxide is 0% by mass, or more than 0% by mass but not more than 7% by mass in terms of ZrO2, and the content of the phosphorus oxide is from 3% by mass to 14%by mass in terms of PO4.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an Al-P composite oxide and an exhaust gas purifying catalyst using the same. [Background technology]

[0002] As regulations on automobile exhaust gases become stricter, there is a growing demand for maintaining exhaust gas purification performance over a long period of time. This means that there is a demand for extending the life of catalysts as aftertreatment devices for purifying exhaust gases, that is, improving the long-term durability of catalysts.

[0003] It is known that one of the causes of the decline in exhaust gas purification performance is the reduction in the surface area of ​​refractory inorganic oxide particles (e.g., alumina, etc.) used as a carrier for precious metals, etc., due to long-term exposure to high-temperature exhaust gas. particle Regarding the above, measures for suppressing the decrease in surface area after endurance at high temperatures have been investigated.

[0004] For example, JP 2004-167354 A discloses a catalyst carrier in which phosphorus is added to a composite oxide containing Al2O3 and an acidic oxide composed of at least one of ZrO2 and TiO2. According to JP 2004-167354 A, the catalyst carrier contains P, which brings the precious metal into a highly oxidized state, and the large surface area of ​​the carrier after high-temperature durability inhibits the grain growth of the precious metal, so that the catalyst carrier can exhibit high NO oxidation activity even at low temperatures even after high-temperature durability. Summary of the Invention [Problem to be solved by the invention]

[0005] However, according to the study by the present inventors, it was found that even with the technology described in JP 2004-167354 A, there are cases where sufficient exhaust gas purification performance cannot be achieved. In particular, the oxidation performance of carbon monoxide (CO) and hydrocarbons (HC) in the low temperature range after high temperature durability is insufficient, and therefore improvement is required.

[0006] Therefore, an object of the present invention is to provide a means for improving the oxidation performance of CO and HC in a low temperature range even after high temperature durability in an exhaust gas purification catalyst.

Means for Solving the Problems

[0007] The inventors of the present invention conducted intensive research to solve the above problems. As a result, in an Al-P composite oxide containing aluminum oxide and phosphorus oxide, in addition to setting the contents of aluminum oxide and phosphorus oxide within a predetermined range, by setting the content of zirconium oxide to a value equal to or less than a predetermined value, it was found that the above problems can be solved, and the present invention has been completed.

[0008] That is, one embodiment of the present invention is an Al-P composite oxide containing aluminum oxide and phosphorus oxide, wherein the content of the aluminum oxide is 79% by mass or more and 97% by mass or less in terms of Al2O3, the content of zirconium oxide is 0% by mass or more than 0% by mass and 7% by mass or less in terms of ZrO2, and the content of the phosphorus oxide is 3% by mass or more and 14% by mass or less in terms of PO4, based on the total mass of the Al-P composite oxide.

Embodiments for Carrying Out the Invention

[0009] The numerical range "A to B" in this specification means "A or more and B or less". Also, "A and / or B" means "either A or B" or "both A and B". In addition, unless otherwise specified, various physical properties in this specification mean values measured by the methods described in the examples below.

[0010] <Al-P composite oxide> An Al-P composite oxide (hereinafter simply referred to as "composite oxide") according to one embodiment of the present invention contains aluminum oxide and phosphorus oxide, and is characterized in that, relative to the total mass of the Al-P composite oxide, the content of the aluminum oxide is 79 mass% or more and 97 mass% or less in terms of Al2O3, the content of the zirconium oxide is 0 mass% or more and 7 mass% or less in terms of ZrO2, and the content of the phosphorus oxide is 3 mass% or more and 14 mass% or less in terms of PO4. By having the above-mentioned configuration, the Al-P composite oxide according to the present invention can improve the oxidation performance of HC and CO at low temperatures in an exhaust gas purification catalyst even after high-temperature durability.

[0011] The Al-P composite oxide according to the present invention essentially contains aluminum oxide (alumina). The content of aluminum oxide is 79% by mass or more and 97% by mass or less, preferably 85% by mass or more and 95% by mass or less, more preferably 85% by mass or more and 90% by mass or less, and further preferably 85% by mass or more and less than 90% by mass, calculated as Al2O3, based on the total mass of the Al-P composite oxide. If the content of aluminum oxide is less than 79% by mass, the high-temperature durability is reduced, which is undesirable. If the content of aluminum oxide is more than 97% by mass, the effect of phosphorus oxide is reduced, which is undesirable.

[0012] The Al-P composite oxide according to the present invention essentially contains phosphorus oxide. The content of phosphorus oxide is 3% by mass or more and 14% by mass or less, and preferably 5% by mass or more and 10% by mass or less, calculated as PO4, based on the total mass of the Al-P composite oxide. If the content of phosphorus oxide is less than 3% by mass, the acid sites of the Al-P composite oxide are insufficient, and the adhesion function of water (H2O) and low-reactivity HC (high boiling point HC, aromatic HC, etc.) to the acid sites is reduced, which is undesirable because adhesion of water (H2O) and low-reactivity HC (high boiling point HC, aromatic HC, etc.) to the precious metal adsorbed on Al is promoted. If the content of phosphorus oxide is more than 14% by mass, the exposed Al decreases with an increase in the surface P concentration, which is undesirable because the dispersibility of the precious metal is significantly reduced. Note that, as shown in the examples described later, a particularly high HC and CO oxidation rate is achieved when the content of phosphorus oxide is in the range of 7.5% by mass or more and 10% by mass or less, calculated as PO4, based on the total mass of the Al-P composite oxide. On the other hand, the value of "CO and HC oxidation performance per unit PO4 amount" calculated in the examples described later is particularly high when the phosphorus oxide content is in the range of 5 mass% to 7.5 mass% inclusive, calculated as PO4, relative to the total mass of the Al-P complex oxide. Since the value of "CO and HC oxidation performance per unit PO4 amount" is an index showing the degree of improvement in exhaust gas purification performance by PO4, when the balance between the improvement effect of exhaust gas purification performance and the cost of the phosphorus oxide raw material (phosphorus source) is taken into consideration, the range of 5 mass% to 7.5 mass% inclusive is said to be particularly preferable.

[0013] The Al-P composite oxide according to the present invention preferably contains zirconium oxide. It is preferable that the Al-P composite oxide contains zirconium oxide because it can maintain a high specific surface area. When the Al-P composite oxide contains zirconium oxide, the content of zirconium oxide is 7 mass% or less, preferably 5 mass% or less, calculated as ZrO2, based on the total mass of the Al-P composite oxide. When the content of zirconium oxide is 7 mass% or less, the phase transition of aluminum oxide under high temperature durability can be suppressed, and a high specific surface area can be maintained. That is, the numerical range of the content of zirconium oxide in the Al-P composite oxide according to the present invention is 0 mass% or more than 0 mass% and 7 mass% or less, preferably 0 mass% or more than 0 mass% and 6 mass% or less, more preferably 0 mass% or more and 5 mass% or less, calculated as ZrO2, based on the total mass of the Al-P composite oxide.

[0014] In a preferred embodiment of the Al-P composite oxide of the present invention, the aluminum oxide content is 85% by mass or more and 95% by mass or less, calculated as Al2O3, the zirconium oxide content is 0% by mass or more and 5% by mass or less, calculated as ZrO2, and the phosphorus oxide content is 5% by mass or more and 10% by mass or less, calculated as PO4, relative to the total mass of the Al-P composite oxide.

[0015] The Al-P composite oxide according to the present invention may contain other metal oxides. Examples of other metal oxides include silicon dioxide (silica; SiO2) and titanium oxide (titania; TiO2). However, from the viewpoint of further improving the effects of the present invention, the content of other metal oxides is preferably 0 mass% or more than 0 mass% and not more than 10 mass%, more preferably 0 mass% or more than 0 mass% and not more than 5 mass%, and even more preferably 0 mass% (not including other metal oxides) based on the total mass of the Al-P composite oxide. That is, the Al-P composite oxide according to a preferred embodiment of the present invention contains only aluminum oxide and phosphorus oxide, or contains only aluminum oxide, phosphorus oxide, and zirconium oxide.

[0016] The contents of aluminum oxide, phosphorus oxide, zirconium oxide and other metal oxides contained in the Al-P composite oxide can be controlled by adjusting the amount of raw materials (metal sources) used in producing the Al-P composite oxide. The contents of these elements contained in the Al-P composite oxide can be measured by inductively coupled plasma optical emission spectroscopy (ICP-OES).

[0017] The specific surface area of ​​the Al-P composite oxide can be measured by a multipoint BET method in accordance with ISO 9277:2010. The BET specific surface area of ​​the Al-P composite oxide (BET surface area per 1 g of the Al-P composite oxide) is preferably 170 m 2 / g or more 300m 2 / g or less, more preferably 170m 2 / g or more 280m 2 / g or less, more preferably 170m 2 / g or more 260m 2 / g or less, and particularly preferably 190m 2 / g or more 250m 2 / g or less. The BET specific surface area of ​​the Al-P composite oxide is 170 m 2 A BET specific surface area of ​​the Al-P composite oxide of 300 m / g or more is preferable because the precious metal supported on the Al-P composite oxide is highly dispersed. 2 / g It is preferable that the Al-P composite oxide has a BET specific surface area of ​​less than 100 nm when exposed to high-temperature exhaust gas.

[0018] The amount of acid sites of the Al-P composite oxide can be measured by the ammonia (NH3) TPD method. The amount of NH3 desorption obtained by the NH3 TPD method correlates with the amount of acid sites present on the surface of the Al-P composite oxide. The larger the amount of NH3 desorption, the larger the amount of acid sites present on the surface of the Al-P composite oxide. If the amount of acid sites present on the surface of the Al-P composite oxide is different, the characteristics of the Al-P composite oxide will be different, and the state of the precious metal supported thereon will also be different. The amount of NH3 desorption is preferably 43 μmol or more and 150 μmol or less per 1 g of the Al-P composite oxide, more preferably 45 μmol or more and 100 μmol or less, even more preferably 48 μmol or more and 80 μmol or less, and particularly preferably more than 50 μmol and 80 μmol or less. If the amount of NH3 desorbed per 1 g of the Al-P composite oxide is 43 μmol or more, the precious metal is supported near the acid sites, and the precious metal is likely to maintain a zero-valent state with high catalytic activity. When the precious metal maintains a zero-valence state, the H2O adsorbed on the precious metal migrates and adsorbs to the acid sites on the P atoms present on the surface of the Al-P composite oxide, which promotes the oxidation reaction of CO and HC on the precious metal, which is preferable. On the other hand, when the amount of NH3 desorbed per 1 g of Al-P composite oxide is 150 μmol or less, the distance between adjacent acid sites is maintained, which suppresses the aggregation of the precious metal on the surface of the Al-P composite oxide. This is preferable because the precious metal is supported on the surface of the Al-P composite oxide in a highly dispersed state. In other words, when the amount of NH3 desorbed is in this range, Al and P on the surface of the Al-P composite oxide are arranged at an appropriate interval. As a result, the CO and HC oxidation activity performance can be improved.

[0019] The method for producing the Al-P composite oxide according to the present invention is not particularly limited, and any method for producing a composite oxide that can be used in the present technical field can be appropriately adopted. For example, the method for producing a composite oxide includes a precipitation method, a hydrolysis method, a sol-gel method, a hydrothermal synthesis method, etc. Among these, it is preferable to use the precipitation method in order to obtain a more uniform Al-P composite oxide.

[0020] The raw material used for producing the Al-P composite oxide is not particularly limited, and raw materials that can be used in the present technical field can be appropriately adopted. Examples of the raw material for alumina (aluminum source) include alumina such as γ-alumina, δ-alumina, and θ-alumina, as well as aluminum chloride, aluminum nitrate (e.g., aluminum nitrate nonahydrate), aluminum sulfate, aluminum acetate, and aluminum hydroxide, which become alumina when fired. Among these, aluminum nitrate (e.g., aluminum nitrate nonahydrate) is preferred. Examples of the raw material for zirconia (zirconium source) include oxides such as zirconia and zirconia sol, as well as zirconium oxynitrate, zirconium oxychloride, zirconium nitrate, basic zirconium sulfate, zirconium carbonate, and zirconium hydroxide, which become zirconia when fired. Among these, zirconium nitrate is preferred. Examples of the raw material for phosphorus oxide (phosphorus source) include phosphoric acid, phosphorous acid, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate. Among these, phosphoric acid is preferred.

[0021] For example, in a method for producing an Al-P composite oxide by a precipitation method, necessary raw materials are dissolved in water to prepare an acidic mixed aqueous solution, and then the mixed aqueous solution is dropped into an alkaline aqueous solution such as ammonia water to generate a precipitate. In order to arrange an appropriate amount of phosphorus atoms on the surface of alumina after drying or calcination, an appropriate amount of solvent (e.g., water) is used during precipitation. If the amount of solvent (e.g., water) is small, the phosphorus concentration on the alumina surface becomes high, and if it is too much, the surface phosphorus concentration tends to decrease and the solvent discharge amount becomes large, which is inappropriate from the viewpoint of production. The amount of the solvent is preferably 1 to 10 mass %, more preferably 2 to 8 mass %, based on the amount of Al-P composite oxide after calcination described below (oxide equivalent). Then, the obtained precipitate is dried and then calcined. The drying temperature is preferably 50 to 250°C, more preferably 100 to 200°C, and the drying time is preferably 1 minute to 36 hours, more preferably 5 minutes to 12 hours. The firing is usually carried out in air, the firing temperature is preferably 300 to 1000° C., more preferably 350 to 850° C., and the firing time is preferably 5 minutes to 10 hours, more preferably 10 minutes to 5 hours.

[0022] <Exhaust gas purification catalyst> As described above, the Al-P composite oxide according to the present invention has a large specific surface area and a large amount of solid acid (acid sites), so that the precious metal that catalyzes the oxidation reaction of CO and HC can be highly dispersed. Furthermore, the Al-P composite oxide has an adsorption function for water (H2O) and HC with low reactivity (high boiling point HC, aromatic HC, etc.) on the acid sites, so that the adhesion of water (H2O) and HC with low reactivity (high boiling point HC, aromatic HC, etc.) to the precious metal can be suppressed. These conditions are maintained even after high temperature durability. Therefore, the Al-P composite oxide according to the present invention is suitably used as a catalyst for purifying exhaust gas. That is, according to another embodiment of the present invention, there is provided a catalyst for purifying exhaust gas, in which the Al-P composite oxide and the precious metal are supported on a refractory three-dimensional structure. Preferably, at least a part of the precious metal is supported on the Al-P composite oxide.

[0023] [Al-P composite oxide] Al-P composite oxides function as supports for precious metals in exhaust gas purification catalysts.

[0024] In the exhaust gas purification catalyst according to the present invention, the content (supported amount) of the Al-P composite oxide is preferably 10 to 300 g, more preferably 30 to 150 g, and even more preferably 50 to 80 g per 1 L of the refractory three-dimensional structure. When the content of the Al-P composite oxide is 10 g or more, the effect of the present invention is more effectively exhibited, which is preferable. When the content of the Al-P composite oxide is 300 g or less, the catalyst layer does not become too thick, which is preferable because the exhaust gas can be smoothly circulated.

[0025] [Precious metals] In exhaust gas purification catalysts, precious metals function as catalysts for the oxidation reaction of carbon monoxide (CO) and hydrocarbons (HC) contained in exhaust gas, and the reduction reaction of nitrogen oxides (NOx).

[0026] The noble metal is preferably at least one selected from platinum (Pt), palladium (Pd) and rhodium (Rh), more preferably includes Pt, further preferably includes Pt and Pd, and particularly preferably includes Pt and Pd.

[0027] When the precious metal includes platinum and palladium (preferably platinum and palladium), the mass ratio of platinum and palladium is, in terms of metal, preferably Pt:Pd=1:0.02-1, more preferably Pt:Pd=1:0.04-1, even more preferably Pt:Pd=1:0.1-1, particularly preferably Pt:Pd=1:0.2-1, and most preferably Pt:Pd=1:0.3-0.7. When the mass ratio of platinum and palladium is within the above range, sufficient CO and HC oxidation performance can be exhibited even after heat durability, which is preferable. In this embodiment (when the precious metal includes platinum and palladium (preferably platinum and palladium)), the crystallite size of the precious metal is preferably 1 nm or more and 13 nm or less, more preferably 2.0 nm or more and less than 13.0 nm. As described in the Examples below, the crystallite size is determined by subjecting the catalyst to high-temperature treatment, followed by XRD measurement using CuKα radiation, and then calculating the crystallite size from the half-width of the peak at 2θ=39.86° using the Scherrer formula.

[0028] The peak at 2θ=39.86° is attributed to the Pt(111) plane. Precious metals may include Pt alone, Pd alone, and Pt-Pd alloys, and these peaks may be observed overlapping at around 2θ=40°. In this specification, the crystallite diameter calculated from the half-width of the peak at 2θ=39.86° is defined as the "crystallite diameter of the precious metal", regardless of the position of the peak top actually observed.

[0029] When the precious metal includes platinum and palladium (preferably platinum and palladium), the platinum and palladium content (total loading amount) is preferably 0.1 to 15 g, more preferably 1 to 10 g, and even more preferably 0.5 to 5 g per 1 L of catalyst. If the platinum and palladium content is 0.1 g or more, it is preferable because it is difficult to be subjected to electrostatic interaction from the Al-P composite oxide, and therefore sufficient CO and HC oxidation performance can be exhibited. If the platinum and palladium content is 15 g or less, it is preferable because the dispersion of the precious metal can be kept high.

[0030] The raw material of the precious metal is not particularly limited, and any raw material that can be used in the present technical field can be appropriately adopted. For example, nitrates, acetates, ammonium salts, amine salts, carbonates, etc. of each precious metal can be suitably used.

[0031] [Zeolite] The exhaust gas purifying catalyst according to the present invention preferably contains zeolite (hydrated aluminosilicate). Zeolite has a function of adsorbing HC, and therefore can further improve the HC oxidation performance of the exhaust gas purifying catalyst.

[0032] The type of zeolite is not particularly limited, and may be either natural or synthetic.Specific examples include A-type, X-type, Y-type, L-type, beta-type (BEA-type), ZSM-type, CHA-type, ferrierite-type, Linde-type, faujasite-type, MCM-22-type, and mordenite-type.Of these, beta-type (BEA-type) is preferred.

[0033] The BET specific surface area of ​​the zeolite is preferably 320 to 830 m 2 / g, more preferably 500 to 650 m 2 When the BET specific surface area is within the above range, HC in the exhaust gas can be sufficiently adsorbed.

[0034] The shape of the zeolite is not particularly limited, and may be any shape, such as granular, fine particle, powder, cylindrical, conical, prismatic, cubic, pyramidal, or irregular, but is preferably granular, fine particle, or powder, and more preferably powder.

[0035] The content (loading amount) of zeolite is preferably 0 g or more than 0 g and 300 g or less, more preferably 10 to 60 g, per 1 L of the refractory three-dimensional structure. If the content of zeolite is more than 0 g, it is preferable because it exerts the adsorption effect of HC. If the content of zeolite is 300 g or less, it is preferable because the catalyst layer does not become too thick and the exhaust gas can flow well.

[0036] When the exhaust gas purification catalyst according to the present invention contains zeolite, the mass ratio of the Al-P composite oxide to the zeolite is preferably Al-P composite oxide:zeolite=1:0.05 to 15, more preferably Al-P composite oxide:zeolite=1:0.1 to 1, and further preferably Al-P composite oxide:zeolite=1:0.5 to 0.8. When the mass ratio of the Al-P composite oxide to the zeolite is within the above range, the precious metal can be highly dispersed and HC in the exhaust gas can be sufficiently adsorbed.

[0037] [Co-catalyst] The exhaust gas purification catalyst according to the present invention preferably contains at least one promoter selected from the group consisting of Group 1 elements, Group 2 elements, and rare earth elements. Specific elements include potassium, magnesium, calcium, strontium, barium, lanthanum, and the like. As raw materials, oxides, sulfates, carbonates, nitrates, and the like of Group 1 elements, Group 2 elements, and rare earth elements are used, and after calcination, they are contained in the catalyst in the form of oxides, sulfates, or carbonates. Among them, lanthanum oxide (La2O3), barium oxide (BaO), and barium sulfate (BaSO4) are preferred, and lanthanum oxide (La2O3) is more preferred. The content of the promoter (preferably lanthanum oxide (La2O3)) is preferably 1 to 20 g, more preferably 1 to 10 g, and even more preferably 1 to 5 g per 1 L of the refractory three-dimensional structure.

[0038] [Other ingredients] The exhaust gas purification catalyst according to the present invention may contain other components. The other components are not particularly limited, and those that can be used in the present technical field can be appropriately adopted. Specifically, refractory inorganic oxides other than the Al-P composite oxide of the present invention (alumina, lanthanum-containing alumina, zirconia, silica-alumina, titania, etc.) can be mentioned. However, from the viewpoint of further exerting the effects of the present invention, it is preferable that the amount of other components is small. Specifically, the content (support amount) of the other components is preferably 0 to 50 g, more preferably 0 to 10 g, per 1 L of the refractory three-dimensional structure.

[0039] [Fireproof three-dimensional structure] The refractory three-dimensional structure is not particularly limited, and any structure that can be used in the present technical field can be appropriately adopted, but is preferably a honeycomb carrier. Examples of honeycomb carriers include monolith honeycomb carriers, metal honeycomb carriers, and plug honeycomb carriers such as particulate filters. Examples of materials for honeycomb carriers include cordierite, silicon carbide, silicon nitride, stainless steel, and heat-resistant metals such as Fe-Cr-Al alloys.

[0040] The honeycomb carrier is manufactured by extrusion molding or by winding sheet-like elements. The shape of the gas passage opening (cell shape) may be any of hexagonal, rectangular, triangular, and corrugated. A cell density (cell number / unit cross-sectional area) of 100 to 1200 cells / square inch (15.5 to 186 cells / square centimeter) is sufficiently usable, and is preferably 200 to 900 cells / square inch (31 to 139.5 cells / square centimeter).

[0041] The total length of the fire-resistant three-dimensional structure is preferably 10 to 1000 mm, more preferably 15 to 300 mm, and further preferably 20 to 150 mm.

[0042] The method for producing the catalyst for purifying exhaust gas according to the present invention is not particularly limited, and a known method can be appropriately adopted. As a preferred embodiment, there is a method for producing the catalyst for purifying exhaust gas, which includes (a) a slurry preparation step, (b) a slurry application step, and (c) a drying and firing step. Each of the steps (a) to (c) will be described in detail below.

[0043] (a) Slurry preparation process The slurry preparation step is a step of preparing a slurry containing raw materials that will become the aforementioned components (Al-P composite oxide and precious metals, as well as optionally contained zeolite, co-catalyst, and other components) after the drying and firing step described below. The slurry is prepared by mixing the raw materials of each component in an aqueous medium and wet pulverizing the mixture.

[0044] The aqueous medium may be water, a lower alcohol such as ethanol or 2-propanol, an organic alkaline aqueous solution, etc. Among these, it is preferable to use water and / or a lower alcohol, and it is more preferable to use water.

[0045] The wet grinding can be carried out by a known method using, for example, a ball mill.

[0046] In the slurry preparation step, each component is added to an aqueous medium, stirred for 5 minutes to 24 hours, and then wet-pulverized. If the pH of the slurry immediately before wet-pulverization is 10 or higher, the pH can be adjusted to less than 10, preferably less than 8, with an acid such as nitric acid, before wet-pulverization. If the pH of the slurry immediately before wet-pulverization is less than 2, the pH can be adjusted to 2 or more, preferably 4 or more, with a base such as ammonia water, before wet-pulverization.

[0047] In addition, when the exhaust gas purification catalyst has two or more catalyst layers, a slurry is prepared for each catalyst layer. For example, when the catalyst has two catalyst layers (a lower catalyst layer and an upper catalyst layer), a first slurry for forming the lower catalyst layer and a second slurry for forming the upper catalyst layer are prepared in the slurry preparation step. The first slurry and the second slurry can have different compositions.

[0048] (b) Slurry application process The slurry application step is a step of applying the slurry obtained in the slurry preparation step onto the refractory three-dimensional structure. A known method can be appropriately adopted as a method for applying the slurry onto the refractory three-dimensional structure. In addition, the amount of the slurry applied can be appropriately set by a person skilled in the art depending on the amount of solids in the slurry and the thickness of the catalyst layer to be formed.

[0049] (c) Drying and firing process The drying and firing process is a process of drying and firing the slurry applied on the refractory three-dimensional structure in the slurry application process. The drying and firing process may be performed separately as a drying process and a firing process, but as long as each component can be supported on the refractory three-dimensional structure, the drying and firing processes may be performed by a single heat treatment without distinguishing between the drying and firing processes.

[0050] In the drying step, the slurry is dried in air at a temperature of preferably 50 to 300° C., more preferably 80 to 200° C., for preferably 5 minutes to 10 hours, more preferably 30 minutes to 8 hours.

[0051] In the firing step, the slurry dried in the drying step is fired in air at a temperature of preferably 300 to 1200° C., more preferably 400 to 700° C., for preferably 10 minutes to 10 hours, more preferably 30 minutes to 5 hours.

[0052] When two catalyst layers are formed on the refractory three-dimensional structure, the first slurry is applied onto the refractory three-dimensional structure, a drying and firing process is performed to form a lower catalyst layer, and then the second slurry is applied onto the lower catalyst layer, and a drying and firing process is performed to form an upper catalyst layer. This makes it possible to manufacture a catalyst for purifying exhaust gas in which two layers, the lower catalyst layer and the upper catalyst layer, are laminated on the refractory three-dimensional structure. When the thickness of the catalyst layer is to be increased, the above steps (a) to (c) can be repeated using the same slurry.

[0053] <Method of purifying exhaust gas> According to another aspect of the present invention, there is provided a method for purifying exhaust gas, comprising contacting the above-mentioned exhaust gas purification catalyst with exhaust gas discharged from an internal combustion engine. Examples of the internal combustion engine include diesel engines, diesel hybrid engines, and engines that use natural gas or the like as fuel. Among these, diesel engines are preferred.

[0054] The space velocity (SV) of the exhaust gas may be a normal velocity, but is preferably 1,000 to 500,000 h -1 , more preferably 5,000 to 200,000 hours -1 The linear velocity of the gas may also be a normal velocity, but is preferably 0.1 to 8.5 m / sec, more preferably 0.2 to 6.7 m / sec during contact.

[0055] According to the present invention, even after high-temperature endurance, the oxidation performance of CO and HC in a low temperature range can be improved. Here, high-temperature endurance is preferably performed by exposing the catalyst to an atmosphere of 650 to 1200°C for 5 to 500 hours, more preferably to an atmosphere of 650 to 800°C for 10 to 100 hours. That is, according to a preferred embodiment of the present invention, there is provided a method for purifying exhaust gas, which includes exposing the above-mentioned exhaust gas purification catalyst to an atmosphere of 650 to 1200°C for 5 to 500 hours, and then contacting the catalyst with exhaust gas discharged from an internal combustion engine.

[0056] To measure the oxidation rate of CO and HC in exhaust gas using a diesel engine, it is preferable to use an evaluation mode for exhaust gas regulations, such as the NEDC (New European Driving Cycle) mode, JC08 mode, WLTC, FTP75, FTP1199, NRTC, NRSC mode, etc. For example, when performing evaluation in the NEDC mode, it is in accordance with Addendum 82: Regulation No. 83 of the United Nations Economic Commission for Europe.

[0057] Furthermore, according to the present invention, even after high-temperature durability, excellent purification performance (particularly, oxidation performance of CO and HC) can be exhibited for low-temperature exhaust gas. Here, the low temperature is preferably in the range of 50 to 600°C, more preferably 50 to 400°C. That is, according to a preferred embodiment of the present invention, there is provided a method for purifying exhaust gas, which comprises exposing the above-mentioned exhaust gas purification catalyst to an atmosphere of 650 to 1200°C for 5 to 500 hours, and then contacting the catalyst with exhaust gas of 50 to 600°C discharged from an internal combustion engine.

[0058] In this specification, the term "exhaust gas temperature" refers to the temperature of the exhaust gas at the catalyst inlet. Here, the term "catalyst inlet" refers to the portion of the exhaust pipe in which the exhaust gas purification catalyst is installed, extending from the catalyst end face on the exhaust gas inlet side toward the internal combustion engine by up to 10 cm, and also refers to the central portion in the longitudinal (axial) direction of the exhaust pipe. EXAMPLES

[0059] Hereinafter, the present invention will be described more specifically with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples. Unless otherwise specified, each operation was carried out under the conditions of room temperature (25°C) / relative humidity 40 - 50%RH. Also, unless otherwise specified, the ratio represents the mass ratio.

[0060] <Production of Al-P Composite Oxide> [Example 1] As the alumina raw material, aluminum nitrate nonahydrate, as the zirconia raw material, zirconium nitrate, and as the phosphorus oxide raw material, phosphoric acid were weighed so that the mass ratio of Al2O3:ZrO2:PO4 was 90:5:5. Distilled water amounting to 3% by mass with respect to the amount of the Al-P composite oxide (in terms of oxide) after firing was weighed. The weighed alumina raw material was dispersed in distilled water, and further zirconium nitrate and phosphoric acid were added and stirred well to prepare a mixed aqueous solution. This mixed aqueous solution was dropped into an aqueous solution at 25°C adjusted to pH 10 with aqueous ammonia. During the dropping, the pH of the solution was adjusted with aqueous ammonia so as to be in the range of 7 - 10. After the dropping was completed, the resulting precipitate was collected by filtration and washed well with deionized water. Next, this was dried at 150°C for 8 hours and then fired in air at 850°C for 1 hour to obtain the Al-P composite oxide powder a.

[0061] [Examples 2 - 5, Comparative Examples 1 - 6] Powders b - k were obtained in the same manner as in Example 1, except that the alumina raw material, zirconia raw material, and phosphorus oxide raw material were weighed so that the ratio of Al2O3:ZrO2:PO4 was the value shown in Table 1 below.

[0062] [Comparative Example 7] As the alumina raw material, aluminum nitrate nonahydrate, as the zirconia raw material, zirconium nitrate, as the silica raw material, sodium metasilicate, and as the titania raw material, titanium sulfate were weighed so that the ratio of Al2O3:ZrO2:SiO2:TiO2 was 90:5:2.5:2.5, and in the same manner as in Example 1, the Al-Zr-Si-Ti composite oxide powder l was obtained.

[0063] <Evaluation> [BET specific surface area] The BET specific surface area of ​​the Al-P composite oxide was measured in accordance with ISO 9277:2010. Specifically, an automatic specific surface area / pore distribution analyzer (Tristar II3020, manufactured by Micromeritics) was used to fill a sample cell with 0.05 g of the Al-P composite oxide, and the BET specific surface area of ​​the Al-P composite oxide was measured by the BET multipoint method. The results are shown in Table 1 below.

[0064] [Solid acid amount (NH3 release amount)] The solid acid amount of the Al-P composite oxide was measured using an ammonia temperature programmed desorption method (ammonia TPD method). Specifically, 50 mg of the Al-P composite oxide sufficiently crushed in an agate mortar was used as a sample, and pre-treated by standing under a helium flow at 600°C for 30 minutes. The sample was cooled, and a mixed gas of ammonia and helium (ammonia concentration 5.0% by volume) was passed through it at 50°C for 30 minutes to saturate and adsorb ammonia to the sample. After that, helium was passed through it at 50°C for 30 minutes to purge ammonia other than that adsorbed on the sample. Then, the sample was heated from 50°C to 600°C at a heating rate of 10°C / min under helium flow, and the amount of ammonia desorbed during the heating process was measured using a quadrupole mass spectrometer (BELMass, manufactured by Microtrac). At this time, the amount of ammonia was calculated from the relationship (calibration curve) between the ion intensity of the mass spectrometer and the amount of ammonia for ammonia, which was previously obtained using a helium mixed gas containing ammonia of known concentration. The results are shown in Table 1 below. The greater the amount of desorbed ammonia, the greater the amount of solid acid.

[0065] <Production of exhaust gas purification catalysts> [Catalyst A~L] Exhaust gas purifying catalysts A to L were produced using Al-P composite oxide powders a to l, respectively. Platinum nitrate was used as the Pt raw material, palladium nitrate was used as the Pd raw material, and each Al-P composite oxide powder was used. Powdered beta zeolite (silica / alumina (molar ratio): 35 to 40, BET specific surface area: 550 to 600 m) was used as the zeolite raw material. 2 / g, average secondary particle diameter: 2-6μm), and lanthanum oxide as a lanthanum oxide raw material were weighed out so that the mass ratio of Pt:Pd:Al-P composite oxide:zeolite:La2O3 was 1.33:0.67:60:40:2. The weighed raw materials were added to deionized water, stirred for 30 minutes, and then adjusted to pH 5 by adding nitric acid to obtain a dispersion. Next, this dispersion was wet-pulverized in a ball mill at a rotation speed of 200 rpm for 30 minutes to prepare a slurry. Next, this slurry was wash-coated onto a cylindrical cordierite carrier (number of cells: 400 cells per square inch of cross-sectional area (1 inch = 2.54 cm)) with a diameter of 129 mm and a length of 70 mm, and 0.9 L, so that the loading amount after firing was 104.0 g per liter of the carrier. Next, the catalysts were obtained by drying at 150°C for 20 minutes and then calcining in air at 500°C for 1 hour.

[0066] [Catalyst B1] Catalyst B1 was obtained in the same manner as catalyst B, except that the Pt raw material, Pd raw material, powder b, zeolite raw material, and lanthanum oxide raw material were each weighed so that the mass ratio of Pt:Pd:powder b:zeolite:La2O3 was 1.20:0.80:60:40:2.

[0067] [Catalyst B2] Catalyst B2 was obtained in the same manner as catalyst B, except that the Pt raw material, Pd raw material, powder b, zeolite raw material, and lanthanum oxide raw material were each weighed so that the mass ratio of Pt:Pd:powder b:zeolite:La2O3 was 1.50:0.50:60:40:2.

[0068] [Catalyst B3] Catalyst B3 was obtained in the same manner as catalyst B, except that the Pt raw material, Pd raw material, powder b, zeolite raw material, and lanthanum oxide raw material were each weighed so that the mass ratio of Pt:Pd:powder b:zeolite:La2O3 was 1.71:0.29:60:40:2.

[0069] <Evaluation> [High temperature durability] The exhaust gas purification catalyst was subjected to high temperature treatment in air at 700°C for 50 hours using an electric furnace.

[0070] [Crystallite diameter of precious metals] The crystallite size of the precious metal contained in the exhaust gas purification catalyst after high-temperature treatment was measured using the X-ray diffraction (XRD) method. The measurement was performed in accordance with JIS H7805:2005 using an X-ray diffractometer (Expert Pro, manufactured by Spectris). The measurement conditions were as follows: measurement angle range (2θ): 30° to 50°, step interval: 0.02°, measurement time: 200 seconds / step, radiation source: CuKα radiation, tube voltage: 45 kV, current: 40 mA. As a result of the measurement, the crystallite size of the precious metal was calculated using the Scherrer formula from the half-width of the peak at 2θ=39.86° in the obtained diffraction pattern. The results are shown in Tables 1 and 2 below.

[0071] [CO and HC oxidation performance] The CO and HC oxidation performance of the exhaust gas purification catalyst after high temperature treatment was evaluated. Specifically, the catalyst was installed at a position 100 cm behind the exhaust port of a 3.0L turbo diesel engine, and evaluation was performed using the NEDC to measure the CO and HC oxidation rates (%). The exhaust gas temperature was in the range of 25 to 380°C. In addition, the CO and HC oxidation performance per unit PO4 amount of the exhaust gas purification catalyst containing the Al-P composite oxide of the example was calculated using the following formula. The higher the value, the higher the effect of improving the exhaust gas purification performance by PO4.

[0072]

number

[0073] The results are shown in Tables 1 and 2 below.

[0074] [Table 1]

[0075] [Table 2]

[0076] The results in Table 1 show that the Al-P composite oxide according to the present invention has a large BET specific surface area and a large amount of NH3 desorption (solid acid amount) because the contents of aluminum oxide, zirconium oxide and phosphorus oxide are within specific ranges.

[0077] In addition, the results in Table 1 show that the exhaust gas purification catalyst according to the present invention contains the above-mentioned Al-P composite oxide, and therefore the crystallite size of the precious metal is small even after high-temperature durability, and the oxidation rate of CO and HC at low temperatures is significantly improved.

[0078] This application is based on Japanese Patent Application No. 2020-208473, filed on December 16, 2020, the disclosure of which is hereby incorporated by reference in its entirety.

Claims

1. An exhaust gas purification catalyst (excluding those in which the precious metal contains rhodium) comprising an Al-P composite oxide containing aluminum oxide and phosphorus oxide and a precious metal supported on a refractory three-dimensional structure, The content of the aluminum oxide in the Al-P composite oxide is Al 2 O 3 The zirconium oxide content is 79 mass % or more and 97 mass % or less in terms of zirconium oxide content. 2 The phosphorus oxide content is 0 mass % or more than 0 mass % and 7 mass % or less in terms of PO 4 In terms of mass%, the content is 3% by mass or more and 14% by mass or less, The precious metals include platinum and palladium; The mass ratio of the platinum to the palladium is Pt:Pd=1:0.1 to 1 in terms of metal, The exhaust gas purification catalyst is subjected to high-temperature treatment in air at 700° C. for 50 hours using an electric furnace, and then subjected to XRD measurement using CuKα radiation. The crystallite size calculated using Scherrer's formula from the half-width of the peak at 2θ=39.86° assigned to the Pt(111) plane is 1 to 13 nm.

2. The content of the aluminum oxide in the Al-P composite oxide is Al 2 O 3 The zirconium oxide content is 85 mass % or more and 95 mass % or less in terms of ZrO 2 The phosphorus oxide content is 0 mass % or more than 0 mass % and 5 mass % or less in terms of PO 4 The exhaust gas purifying catalyst according to claim 1 , wherein the total amount of the carbon black is 5% by mass or more and 10% by mass or less in terms of the total amount of the carbon black.

3. NH of the Al-P composite oxide in ammonia TPD measurement 3 3. The exhaust gas purifying catalyst according to claim 1, wherein the amount of desorption is 43 to 150 μmol / g per 1 g of the Al-P composite oxide.

4. The BET specific surface area of ​​the Al-P composite oxide is 170 to 300 m 2 The exhaust gas purifying catalyst according to any one of claims 1 to 3, wherein the molar ratio of the catalyst to the exhaust gas is 1:1 or more.

5. An exhaust gas purification catalyst described in any one of claims 1 to 4, wherein the mass ratio of the platinum to the palladium is Pt:Pd = 1:0.2-1 in metal conversion.

6. A method for purifying exhaust gas, comprising contacting the exhaust gas purifying catalyst according to any one of claims 1 to 5 with exhaust gas discharged from an internal combustion engine.

Citation Information

Patent Citations

  • Molecular sieve on carrier- palladium-platinum catalyst

    JP1990174937A

  • Phosphate-alumina material with adjusted pore diameter

    JP1994171915A

  • Catalyst for purifying exhaust gas

    JP1999047596A

  • Formed catalyst for hydrogenation treatment and producing method thereof

    JP2002028491A

  • Catalyst for use in hydrogenation purification, method of producing the same, and method of hydrogenating / purifying hydrocarbon oil

    JP2010221117A